Long-term changes in the thermodynamic structure of the lowermost stratosphere inferred from reanalysis data - F. Weyland; P. Hoor; D. Kunkel; T. Birner; T. Birner; F. Plöger; F. Plöger; K. Turhal; K. Turhal (Atmospheric Chemistry and Physics)
The lowermost stratosphere (LMS) plays an important role in stratosphere–troposphere coupling and the Earth's radiation balance. This study investigates the effects of long-term changes in the tropopause and the lower-stratospheric isentropic structure on the mass of the LMS. We compare five modern reanalyses: ERA5, ERA-Interim, MERRA-2, JRA-55 and JRA-3Q. The focus is on changes after 1998, which marks the anticipated beginning of stratospheric ozone recovery. The trend analysis is performed with a dynamic linear regression model (DLM), capable of modeling non-linear trends. According to our study, isentropic pressure in the lower stratosphere (here 380–430 K) shows negative trends in the tropics and positive trends in the extratropics. In the Northern Hemisphere (NH), we find that the extratropical tropopause is rising, accompanied by decreasing pressure at an average rate of −1 hPa per decade. Additionally, our results indicate that the tropical tropopause in the NH has expanded poleward by 0.5° latitude between 1998–2019. In the Southern Hemisphere (SH) extratropics, the lapse rate tropopause shows a downward tendency of up to +2 hPa per decade after 1998, consistent across all reanalyses except JRA-3Q. The tropical tropopause and the cold point is rising, accompanied by decreasing pressure at a rate of ca. −0.5 hPa per decade in all reanalyses. The sign of the tropical tropopause potential temperature trends, however, differs across the reanalyses. This can be attributed to contrasting (absolute) temperature trends in the tropical tropopause region, such as at the 100 hPa pressure level. Consistent with the upward and poleward trend of the NH tropopause, the mass of the LMS decreases by 2 %–3 % for 1998–2019 if a fixed isentrope (380 K) is chosen as the upper LMS boundary. In ERA5, as well as MERRA-2 and ERA-Interim, this mass decline disappears if dynamical upper LMS boundaries are used that take the upward trends of the tropical tropopause into account.